Of democratic governance and revenue: Participatory institutions and tax generation in Brazil. Issue 4 (17th November 2020) - Touchton, Michael; Wampler, Brian; Peixoto, Tiago
Abstract: Governments around the world often struggle to collect tax revenues, thus undermining their ability to build functioning states, deliver basic public goods, and improve human development. This problem is especially acute in the Global South. Within the broader context of representative democracy, many local governments increasingly adopt participatory institutions in the hope that they will improve government responsiveness, service delivery, and their electoral opportunities. We address gaps in knowledge on participatory institutions and tax collection by asking two critical questions: to what extent (if any) do these reforms improve local governance? And how would we know? We draw from an original database on Brazilian Municipalities that includes fiscal, political, and state capacity variables. We find that municipal governments that adopt participatory institutions generate higher tax revenues than comparable governments without these institutions. This article thus provides a novel, thorough assessment of how new participatory institutions affect governance and revenue‐generation.